Symptoms, Sites, and Significance of Mycoplasma genitalium in Men Who Have Sex with Men - Read, Tim R.H. (Emerg Infect Dis, 2019)
During 2016–2017, we tested asymptomatic men who have sex with men (MSM) in Melbourne, Australia, for Mycoplasma genitalium and macrolide resistance mutations in urine and anorectal swab specimens by using PCR. We compared M. genitalium detection rates for those asymptomatic men to those for MSM with proctitis and nongonococcal urethritis (NGU) over the same period. Of 1,001 asymptomatic MSM, 95 had M. genitalium; 84.2% were macrolide resistant, and 17% were co-infected with Neisseria gonorrhoeae or Chlamydia trachomatis. Rectal positivity for M. genitalium was 7.0% and urine positivity was 2.7%. M. genitalium was not more commonly detected in the rectums of MSM (n = 355, 5.6%) with symptoms of proctitis over the same period but was more commonly detected in MSM (n = 1,019, 8.1%) with NGU. M. genitalium is common and predominantly macrolide-resistant in asymptomatic MSM. M. genitalium is not associated with proctitis in this population.